2020
DOI: 10.1186/s13063-020-04299-x
|View full text |Cite
|
Sign up to set email alerts
|

Jiao-tai-wan for insomnia symptoms caused by the disharmony of the heart and kidney: a study protocol for a randomized, double-blind, placebo-controlled trial

Abstract: Background Insomnia seriously affects people’s normal lives and work. However, effective treatment strategies are scarce. The purpose of this study is to explore the efficacy and safety of Jiao-tai-wan (JTW) for ameliorating insomnia symptoms caused by disharmony of the heart and kidney. Design This is a randomized, double-blind, placebo-controlled pilot clinical trial. A total of 124 participants suffering from insomnia symptoms wil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The PSQI score was used to assess sleep quality and severity of sleep disorders in the past 7 days, while the PSG was mainly used to identify the sleep phases, such as REM, NREM, and wakefulness [29,42].…”
Section: Psqi and Psg Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PSQI score was used to assess sleep quality and severity of sleep disorders in the past 7 days, while the PSG was mainly used to identify the sleep phases, such as REM, NREM, and wakefulness [29,42].…”
Section: Psqi and Psg Resultsmentioning
confidence: 99%
“…The inclusion criteria for HKIIPs were as follows: (a) Aged 18-to 60-years-old, right-handed, male and female, in junior high school or above; (b) According to the DSM-V, insomnia was de ned as having di culty falling asleep, staying asleep or having refreshing sleep, occurring 3 or more times per week, for at least 3 months [28]; (c) A PSQI score of greater than or equal to 7 according to the criteria for insomnia described in CCMD-3 [29]; (d) A Disharmony of Heart and Kidney Scoring System score is greater than 9 [29]; (e)Free of any psychoactive medication or hypnotic or cognitive behavioral therapy for insomnia for at least 2 weeks before the study. The brief ow diagram of the study process is shown in Fig.…”
Section: Participantsmentioning
confidence: 99%
“…The PSQI score of HKIIPs decreased significantly after treatment with JTW, reflecting the effectiveness of JTW in treating insomnia. The PSQI score was used to assess sleep quality and severity of sleep disorders in the past one month, while the PSG was mainly used to identify the sleep phases, such as REM, NREM, and wakefulness (Chen et al 2018 ; Zeng et al 2020 ). The PSG results showed no significant difference between the JTW and placebo groups after treatment, which could be due to the little effect of JTW on the sleep structure, or short-term treatment that has no effect on the structure of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria for HKIIPs were as follows: (a) Aged 18- to 60- years-old, right-handed, male and female, in junior high school or above; (b) According to the DSM-V, insomnia was defined as having difficulty falling asleep, staying asleep or having refreshing sleep, occurring 3 or more times per week, for at least 3 months (Seow et al 2018 ); (c) A PSQI score of greater than or equal to 7 according to the criteria for insomnia described in CCMD-3 (Zeng et al 2020 ); (d) A Disharmony of Heart and Kidney Scoring System score is greater than 9 according to the “Guide Principles for Clinical Research of New Drugs of TCM” (Zeng et al 2020 ); (e) Free of any psychoactive medication or hypnotic or cognitive behavioral therapy for insomnia for at least 2 weeks before the study.…”
Section: Methodsmentioning
confidence: 99%
“…The use of standardized HM, in particular, is emphasized to establish an effective HM use strategy for PSI treatment and confirm its expected effectiveness and safety. This review provides clinical information of some candidates for standardized herbal formulas, such as Chaihu-Longgu-muli decoction [66], Ningxin Anshen formula [41], Suanzaoren decoction [85], Jiaotai decoction [86], and insomnia granules. Third, future clinical trials should evaluate the changes in insomnia following the use of objective sleep measurements, such as actigraphy or polysomnography.…”
Section: Implications For Future Research and Practicementioning
confidence: 99%